Efeito da adição de PTFE no fluxo de arames tubulares sobre o arco elétrico em soldagem subaquática molhada - Erriston Campos Amaral (2021)
Several studies over the past few years have shown that electrodes coated with agglomerated PTFE (Polytetrafluoroethylene) in air and wet underwater welding applications have good electric arc stability and low diffusible hydrogen contents and considerable volume fraction of acicular ferrite in the weld metal. These results, together with the fact that the tubular wire welding process has great potential for use in underwater welding, suggest that there are good prospects for the use of PTFE as a flux ingredient for this application. In this work, selfprotected cored wires of the rutile-oxidizing type were developed using PFTE as one of the flux ingredients in concentrations of up to 21%. Welds were carried out in a flat position at a depth of 0.5m using direct current with an electrode connected to the negative pole of the machine (CCEN) and connected to the positive pole of the machine (CCEP). Welding electrical signals were monitored and processed in order to determine the characteristic voltages of the process and quantify the occurrence of short circuit and arc extinction, to determine the stability of the process. The influence of flux composition on the morphology and geometry of the weld bead, hydrogen and oxygen contents and microstructure were also evaluated. The results indicated that for both polarities, the welding current increased with the addition of PTFE to the flux. The additions of PTFE also influenced the increase in penetration and bead reinforcement and decrease in bead width. The amount of diffusible hydrogen and oxygen in the weld metal was also affected by reducing with the addition of PTFE, being more pronounced with CCEN. For all formulations no pore formation was observed. Under the conditions studied, there were no significant differences in the microstructure and hardness of the weld metal with the variation of PTFE in the flux. Furthermore, PTFE did not directly influence the chemical composition of the weld metal. In conclusion, cored wires with additions of PTFE to the flux and in DCEN welding condition showed better operational results and greater reductions in the contents of diffusible hydrogen and oxygen in the weld metal.